Inflación semanal en galletitas: Un enfoque de datos de panel - Leandro Meller; Juan M. C. Larrosa; Fernando Delbianco; Gonzalo Ramírez Mu\~noz de Toro; Juan Ignacio Uriarte (Revista de Métodos Cuantitativos para la Economía y la Empresa, 2021)
– The objective of this contribution is to evaluate the weekly price dynamics of the biscuit sector in the framework of an economy with moderate inflation, such as Argentina. Using weekly frequency data, five versions of the function that relate cookie price weekly variations with their possible determinants are estimated. Four of these estimates have been obtained using generalized least squares (GLS), while the rest corresponds to a specification with random effects (RE). Possible influences of the supply level concentration, the features of each product (size, flavour and type), the exchange market situation, certain temporary effects and the variations in the prices of inputs on the price dynamics of the cookies are identified. However, only the effects of changes in input prices were robust. The sign of these robust effects always coincides with the expected values, with the exception of the case of wheat flour.
Keywords: C33; L11; L13; 330; biscuits; pricing; inflation; Argentina; online data